Modern mediators : intermediaries’ informational roles in sourcing from China - Virtanen, Yuan; Salmi, Asta; Qin, Xiao (Emerald, 2021)
Purpose Sourcing intermediaries, commonly known as agents or trading companies, represent a useful organisational solution for assisting companies to manage supply risks and to overcome the liability of foreignness. However, the landscape of global business is experiencing rapid and fundamental changes, which leads us to ask whether intermediaries will continue to play a role in global sourcing. This paper aims to understand how sourcing intermediaries ensure a lasting position in the changing setting of global sourcing and information sharing. Design/methodology/approach This paper investigates the operations of both Chinese and Nordic (Finnish and Swedish) intermediaries in sourcing from China by analysing qualitative data collected over a period of four years. Findings Through the lens of information asymmetry, this paper identifies four distinct informational roles that are used by intermediaries to reduce information asymmetry between suppliers and buyers located in different countries. The paper also examines intermediaries’ signalling activities under these roles in a cross-border triad. Originality/value The paper contributes to the scientific debate on the usefulness of intermediaries by underlining intermediaries’ informational advantage, which provides a new explanation for the survival of intermediaries in a rapidly changing business context. Additionally, this study contributes to research on intermediation strategies by empirically examining both Chinese and Western intermediaries, highlighting the importance of institutional contexts in affecting intermediaries’ informational roles.
Keywords: Intermediary; Sourcing intermediary; Trading company; Global sourcing; China; Qualitative research; fi=Markkinointi|en=Marketing|